Maximize The Effectiveness Of Digital Content Marketing And Utilitarian To Establish Brand Loyalty And Influence Consumer Decisions - Saputra, Teguh; Raharjo, Pamuji Gesang; Kristiadi, Al Agus (Technium Social Sciences Journal, 2024)
The objective of this investigation is to ascertain the impact of digital content marketing and utilitarian on the decision to become a BRI customer through brand loyalty. BRI Unit Simpangan Depok consumers comprise the population of this investigation. The accidental sampling technique was employed to obtain a sample of 287 respondents for this study. With the assistance of SmartPLS, data analysis was conducted using SEM. The study's findings indicate that brand loyalty is influenced by digital content marketing. Nevertheless, the decision to become a customer is not influenced by digital content marketing, either directly or indirectly, through brand loyalty. Utilitarian influences the decision to become a customer and brand loyalty, but it does not influence the decision to become a customer through brand loyalty. In the interim, the decision to become a customer is not influenced by brand loyalty. To facilitate the process of acquiring customers and cultivating a sense of loyalty to the bank's products and services, BRI must prioritize website content so that consumers can rapidly access and make informed decisions.